Papers in honor of Syd Andersonâ€™s contributions to Bolivian and Neotropical Mammalogy - Salazar Bravo, Jorge; Tarifa, Teresa (THERYA, 2020)
The current issue of Therya includes a number of papers honoring the legacy and notable contributions of Dr. Sydney Anderson (1927-2018) to Bolivian and Neotropical mammalogy. â€œEl Doc,â€ as he was warmly referred to by hordes of Bolivians scientists and students, played a central role in the coming of age of mammalogy in Bolivia. He influenced many aspects of this development, from using his own personal funds to purchase traps and museum cases for the then mammal collection of the Bolivian Museum of Natural History, to serving as a towering example of an unassuming mammalogist who loved and honored his science so much that he enjoyed going out camping and trapping in remote areas of Bolivia for almost three decades from 1964 to 1992, and until he was well into his late 60s.